Khadijah Binti Khuwailid Dan Perannya Dalam Perjuangan Rasulullah SAW - Rohmatul Azizah; Nicky Estu Putu Muchtar (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
Khadijah binti Khuwailid is a noble woman who has her own role in accompanying the struggle of Prophet Muhammad. She is a woman who is firm in her religion and has a high degree of dedication to it. His work in history is expected to be a role model for the people of the Prophet Muhammad, especially Muslim women. The type of research used in this study is library research, which presents data using descriptive analytical methods. The results of this study are hoped to be able to show the reader the roles of Khadijah binti Khuwailid in the struggle of Rasulullah SAW. Those roles include being faithful to accompany and being a support system for Rasulullah SAW when he received the first revelation, pouring out his soul, body, and property to spread Islam, and the success of his business during the tearing of the boycott agreement that was hung on the Kaaba. Khadijah really carried her role as Ummul Mukminin.